A conceptual model of motivational factors of knowledge transfer for hospitals - Al-Dalaien A.A.A.-H.; Drus S.M.; Kasim H. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
Knowledge transfer is vital for the successful organization. Majority of previous studies focused on business and educational organization. Few in the field dealt with knowledge transfer in hospitals. This study aims to develop a conceptual model for knowledge transfer in hospitals. Based on the literature review, this study proposes a conceptual framework for knowledge transfer motivation in hospitals based on three motivational aspects; (i) the extrinsic motivational factors such as the promotions and appraisals, (ii) the intrinsic motivational factors such as the altruism, and absorptive capacity, and (iii) the ideal distribution of extrinsic and intrinsic based on the quality and quantity of knowledge transfer that conducted by the knowledge sources and recipients. The conceptual model was tested using a data collected for a pilot study. BEIESP.